Potential for interspecific hybridization between Zizina emelina and Zizina otis (Lepidoptera: Lycaenidae) - Sakamoto, Yoshiko; Yago, Masaya (Journal of insect conservation, 2017)
Environmental changes such as global warming and biological invasion caused by human activities raise the possibility of secondary contact between the endangered butterfly species Zizina emelina and its sibling species Zizina otis in Japan. To assess the possible risks from their habitats overlapping, we investigated the potential for hybridization and the development of F1 individuals. We observed successful mating of the two sibling species under artificial conditions. The presence of a postzygotic hybridization barrier was supported by the delay of larval development only in females; a delay did not occur in males. Existence of the barrier was also supported by a decreased egg hatching rate in one brood; this was likely associated with infection with Wolbachia , a bacterium manipulating the reproductive capability of its host. The size and wing markings of F1 hybrid individuals were intermediate between those of the two species. These results suggest that, if Z. emelina and Z. otis are distributed sympatrically in the future, there is a possibility of introgression and reproductive interference between the two species, which would increase the risk of decline of each species.